Assessing the Future of Renewable Energy Consumption for United Kingdom, Turkey and Nigeria - Nurcan Kilinc Ata (Foresight and STI Governance, 2018)
The relationship between economic growth and renewable energy (RE) consumption has received enormous attention in the literature. However, there are diverse views about the causality and nature of this relationship. The paper investigates how RE consumption during power generation is affected by economic growth and electricity prices using data from 1990 to 2012. This is conducted by using three case study countries (United Kingdom, Turkey, and Nigeria). Then, a prediction model is developed for the year 2030. The findings in this paper show that RE consumption, for the period under consideration, is significantly determined by income and electricity prices in the long run. These findings support the advantages of government policies encouraging the use of RE by implementing RE markets and RE portfolio standards to not only enhance the security and environmental concerns, but also from a macroeconomic point of view (stable economic growth).